Griffing’s methods: review of their importance and application in conventional plant breeding - Saavedra Guevara, Claudia; Pérez López, Delfina de Jesús; González Huerta, Andrés; Franco Martínez, J. Ramón Pascual; Rubí Arriaga, Martin; Ramírez Dávila, José Francisco (Revista Mexicana de Ciencias Agrícolas, 2021)
The estimation of genetic parameters in plants and animals is of great relevance in the agro-livestock and biological sciences. In this context, the effects and variances of combining ability, heritability, heterosis, response to selection, identification of parents and outstanding simple crosses, as well as the prediction of hybrids of higher production and quality, depend on the type of mating and experimental design selected. This study analyzes Griffing’s four methodologies in relation to those of Hayman and Jinks and Gardner and Eberhart; the assumptions considered in these are underlined and the similarities that exist between them are commented. It includes the eight mathematical models that Griffing discussed and that are frequently used to apply some statistical package, cites some studies carried out in the last decade, and suggests some software for its genetic-statistical analysis.